2019
DOI: 10.1016/j.molcel.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Phage AcrIIA2 DNA Mimicry: Structural Basis of the CRISPR and Anti-CRISPR Arms Race

Abstract: Highlights d Crystal structure of SpyCas9 in complex with sgRNA and suppressor AcrIIA2 d AcrIIA2 recognizes sgRNA-bound SpyCas9 d AcrIIA2 prevents the target DNA search by blocking the PAM recognition residues d AcrIIA2 disables bacterial Cas9 by competing with target dsDNA binding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 37 publications
(57 reference statements)
5
64
3
Order By: Relevance
“…Former mechanistic characterizations of Acr proteins have revealed a remarkable diversity of inhibitory functions (Davidson et al, 2020). Interestingly, relatively low MWs and pIs have been reported for Acrs inhibiting CRISPR-Cas systems via DNA mimicry (Jiang et al, 2019;Liu et al, 2019), suggesting a putative link between low MW/pI values and mechanistic inhibitory function. Given the small size and negative charges of AcrIF18* and AcrIF15 (Supplementary Figure S2), and their Cascade DNA binding inhibitory activities (Supplementary Figure S3), it is possible that they function as DNA mimics -analogous to AcrIF2 (Chowdhury et al, 2017), AcrIF10 (Guo et al, 2017), AcrIIA2 (Shin et al, 2017;Liu et al, 2019) and AcrIIA4 (Dong et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Former mechanistic characterizations of Acr proteins have revealed a remarkable diversity of inhibitory functions (Davidson et al, 2020). Interestingly, relatively low MWs and pIs have been reported for Acrs inhibiting CRISPR-Cas systems via DNA mimicry (Jiang et al, 2019;Liu et al, 2019), suggesting a putative link between low MW/pI values and mechanistic inhibitory function. Given the small size and negative charges of AcrIF18* and AcrIF15 (Supplementary Figure S2), and their Cascade DNA binding inhibitory activities (Supplementary Figure S3), it is possible that they function as DNA mimics -analogous to AcrIF2 (Chowdhury et al, 2017), AcrIF10 (Guo et al, 2017), AcrIIA2 (Shin et al, 2017;Liu et al, 2019) and AcrIIA4 (Dong et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Combining electrophoretic mobility shift assays (EMASs), fluorescence polarization assays and image assays, J. Lee et al showed that both AcrIIC4 and AcrIIC5 prevent NmeCas9 from binding to DNA while having no effect on sgRNA loading . Recently, two structural studies revealed that AcrIIA2 acts as a DNA mimic, blocking the PAM recognition residues and subsequently preventing dsDNA recognition and binding, which is similar to the actions of AcrIIA4 …”
Section: Acr Mechanismsmentioning
confidence: 99%
“…AcrIIA1 acts through a distinct structural and functional characteristic, forming a dimer with a two helical-domain structure and functions via nucleic acid recognition, suggesting that AcrIIA1 functions through a unique mechanism that is not yet clear [78]. A recent approach provided a more detailed mechanism of the AcrIIA2-mediated inhibition of spCas9, showing that AcrIIA2 as a DNA mimic interacts with the PAM recognition residues of Cas9, thereby preventing target dsDNA detection [79]. Basgall et al [80] demonstrated that AcrIIA2 and AcrIIA4 are able to inhibit the functional activity of Cas9 in vivo within haploid yeast and in an active gene-driven system, providing the first documented use of AcrIIA2 and AcrIIA4 to inhibit such a system.…”
Section: Type II Anti-crispr Proteinsmentioning
confidence: 99%